The development of responses to social media reviews in the lodging industry - Bagnera, Suzanne Markham; Schrier, Thomas R.; Arendt, Susan W. (SAGE Business Cases., 2015)
This case study presents information about User-Generated Content (UGC) on social media sites, like TripAdvisor®. This case study aims to familiarize students with social media websites and demonstrate how management should respond to reviews posted by consumers. Examples of positive and negative management responses are provided to help identify appropriate responses. The analysis of management responses will provide students with an opportunity to become familiar with these websites and how they can structure a professional response so they are better prepared to enter the work force with knowledge of UGC.